Young women's religious affiliation and participation as determinants of high school completion - Evelyn Lilian Lehrer (Institute for the Study of Labor (IZA), 2005)
The far-reaching consequences of failing to complete secondary schooling are well known. The central questions addressed in this study are: Does religion make a difference in the likelihood of successfully completing the transition to high-school graduation? If so, how large are the influences? Based on a human capital framework, the paper develops hypotheses about the effects of two dimensions of religion during childhood
Keywords: J24; J15; J22; 330; affiliation and participation